1987
DOI: 10.1243/pime_proc_1987_201_041_02
|View full text |Cite
|
Sign up to set email alerts
|

On the Dynamics and Control of Robotic Manipulators with an Automatic Balancing Mechanism

Abstract: Non-linear characteristics and uncertainty in manipulator dynamics caused by payload effects are major hurdles in controller design. To overcome such hurdles the authors have introduced an automatic balancing concept which has been proved to reduce the non-linear complexity in manipulator dynamics as well as to remove gravity loading. This paper examines the characteristic features of balanced manipulator dynamics in more detail and presents an efficient control algorithm suitable for the dynamics. Since the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…As demonstrated by Tepper and Lowen [27], gravity-balanced manipulators can be designed such that the net torque at each joint in any position is zero under static conditions. Chung and Cho developed a mechanism and control policy for automatically adjusting the distance between counterweights and joints to accommodate a range of payloads [28], and Lim et al investigated potential payload capacity increase using counterbalance mechanisms [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As demonstrated by Tepper and Lowen [27], gravity-balanced manipulators can be designed such that the net torque at each joint in any position is zero under static conditions. Chung and Cho developed a mechanism and control policy for automatically adjusting the distance between counterweights and joints to accommodate a range of payloads [28], and Lim et al investigated potential payload capacity increase using counterbalance mechanisms [29].…”
Section: Introductionmentioning
confidence: 99%
“…When motions are fast, however, dynamic effects increase joint torque requirements due to large counterweight masses (see Lim et al [29]). Gravity force cancellation is easy to design for, and this has been used often as a proxy plant design objective for energy minimization (e.g., Chung and Cho [28], Lim et al [29], Coello et al [30], and Ravichandran et al [31]). While using this proxy plant objective simplifies physical system design, in most cases the resulting systems are suboptimal and do not use minimal energy.…”
Section: Introductionmentioning
confidence: 99%
“…Also, there have been many efforts to reduce the complexities of manipulator dynamics through the physical modification of kinematic and mass distribution structures. 3 " 8 Automatic balancing mechanims (ABM) proposed by Chung and Cho 4 ' 5 has been known to be one of the effectively implementable one among such methods. Chung 4 ' 5 showed that the dynamic characteristics can be greatly enhanced through mass balancing.…”
Section: Introductionmentioning
confidence: 99%
“…3 " 8 Automatic balancing mechanims (ABM) proposed by Chung and Cho 4 ' 5 has been known to be one of the effectively implementable one among such methods. Chung 4 ' 5 showed that the dynamic characteristics can be greatly enhanced through mass balancing. This study, however, was performed without taking into account the joint flexibility, although most conventional manipulators have significant flexibility at their joints.…”
Section: Introductionmentioning
confidence: 99%
“…4 Chung et al have studied the dynamic characteristics and control of balanced robotic manipulators. 5 " 10 They designed mechanical balancing mechanisms implemented on a PUMA-760 robot. The balancing mechanisms were designed basically to compensate for the gravity loadings of the first three links of a PUMA-760 robot.…”
Section: Introductionmentioning
confidence: 99%